(untitled) (Journal of Applied and Natural Science, 2018)
An experiment was conducted at Zonal Agricultural Research Station, V.C farm, Mandya (Karnataka), India during 2015, to assess the chemical control of sugarcane early shoot borer (Chilo infuscatellus). Nine insecticides namely, Fipronil 0.3G, Chlorantraniliprole 0.4G, Chlorantraniliprole 18.5 SC, Spinosad 45SC, Flubendiamide 39.35SC, Cartap hydrochloride 4G, Phorate 10G, Carbofuran 3G, Chlorpyriphos 20EC, and compared with untreated (Check plot)using randomized block design with three replications. Significant differences were noticed among the treatments. Chlorantraniliprole 0.4G recorded lowest cumulative incidence (2.79 %) and highest per cent reduction over the control (85.78 %) which was followed by Cartap hydrochloride 4G (5.37% and 72.65%), Chlorantraniliprole 18.5 SC (5.95% and 75.62%), Flubendiamide 39.35SC (6.64% and 66.19%) and Fipronil 0.3G (6.83% and 65.22%) were found significantly superior in reducing the cumulative incidence of C. infuscatellus.In Co 86032 Cartap hydrochloride 4G was found to be the best insecticide in getting a highest cost benefit ratio (1:12.39). Other insecticides such as Fipronil 0.3G (1:8.84), Chlorantraniliprole 0.4G (1:6.96), Flubendiamide 39.35SC (1:5.42) and Spinosad 45SC (1:4.16) have also recorded better cost benefit ratio. Since Cartap hydrochloride 4G does not have crop label so we can recommend Fipronil 0.3G or Chlorantraniliprole 0.4G for the management of sugarcane early shoot borer.